Managing Learning to Enhance Critical Thinking and Achievement in High School Ecosystem Topics - Nanik Nurhayati; Rif’ati Dina Handayani; Sudarti (Managere: Indonesian Journal of Educational Management, 2025)
This study aims to investigate the impact of learning management systems on the enhancement of critical thinking skills and student learning outcomes in high school ecosystem materials. The research employs a descriptive qualitative approach, utilizing data collection techniques that include in-depth interviews, classroom observations, and documentation. The findings show that the management of learning strategies by teachers, such as the use of case studies, open-ended questions, and group discussions, significantly encourages students to think analytically and reflectively. In addition, the principal plays the role of an instructional leader who fosters an academic climate that promotes critical thinking through teacher training, instructional supervision, and the integration of critical thinking values into the school culture. The learning evaluation system is also directed to assess high-level thinking skills, with the rubric of analysis and reflection as the primary measuring tool. This study concludes that improving learning outcomes cannot be separated from the integration of teacher strategies, school leadership support, and reflection-based evaluation. The study's implications highlight the importance of a holistic managerial approach in science learning, enabling students not only to master concepts but also to develop applicable and contextual critical thinking skills.